THE EFFECT OF ADDITIVE WITH FOAM AGENT AND COCONUT SHELL ON LIGHTWEIGHT CONCRETE - Fikki Efendi; Fredy Kurniawan; Diah Ayu Restuti Wulandari (Neutron, 2019)
Concrete houses have a higher social and economic status. This study provides another consideration for the selection of building materials (Wonorahardjo, 2008). There are several ways that can be used to make concrete lighter, including using lightweight aggregates, substituting coarse aggregates with foam agents, adding coconut shells and additives where coconut shell waste has not been used optimally. In this research, a lightweight concrete mixture made from additives 5M additive, foam agent and coconut shell using 3 kg cement composition. While the 5M additives variation of 3%, 5%, 10%, 15% of cement, 15 milliliters of foam agent and coconut shell of 1%, with consideration of the specimens for 28 days not soaked non-curing. The test specimen is made with a size of 15x30 cm. This study is to determine the weight, compressive strength of the lightweight concrete produced. The results of research on the use of additional 5M additives, foam agents and coconut shells cause concrete to be lighter and compressive strength decreases. The weight of light concrete at 28 days not soaked is 775 kg / cm3, while the quality of concrete is 22 kg / cm2.